VALIDATION AND POPULARIZATION OF IPM TECHNOLOGY IN COTTON THROUGH FARMERS PARTICIPATORY APPROACH IN TRIBAL AREA OF SOUTHERN RAJASTHAN - AMETA, O.P.; SHARMA, K.C.; RANA, B.S.; BAMBAWALE, O.M. (Annals of Agricultural Research, 2014)
The IPM Technology was validated and popularized in village Badgaon, Banswara, Rajasthan through farmers field experiments and farmers fields schools during kharif 2003 and 2004. The IPM module viz., summer ploughing and clean cultivation, early and synchronous sowing of variety G.H.-8, sowing of border trap crop of maize intervene with cowpea all around the cotton field, sowing of setaria in between every 9th and 10th row of cotton which act as a perch crop for birds, installation of pheromone traps all three species of Bollworms @5 traps/ha keeping the height of traps 1 foot above the crop canopy, spray of methyl demeton 25 EC 0.04% at 30 - 35 days after germination, two spray of Neem seed Kernal extract at 45 and 55 days, spray of HaNPV @ 250 LE/ha at 65 DAG, two releases of Trichogramma chilonis @ 1.5 lac/ha at 75 and 85 DAG, need base spray of conventional insecticides was applied in an area of 10 ha field. Farmers field Schools were organized at regular interval to develop the skill and awareness of the farmers about the pests, nature of damage, applicaton of IPM component and natural enemies of the pests. The results of IPM Technology was compared with Non IPM farmers practices which includes 9-10 spray of insecticides. The IPM module reduced the population of sucking insect pests viz., aphids (Aphis gossypii Glover), Jassids (Amrasca bigutulla bigutulla Ishida), White Fly (Bemisia tabaci Genna.), Thrips (Thrips tabaci Lindeman) and bollworms viz., Earias insulana Fab. and Helicoverpa armigera Hub. over non IPM. The mean percent damage to square, flower, green boll, open boll and locule was found less in IPM field as compared to Non IPM fields. The mean seed cotton yield in IPM fields was 1918 and 1804 kg/ha as against 1488 and 1518 kg/ha in non IPM field during 2003 and 2004, respectively. The IPM module also encouraged the population of coccinellids and Chrysoperla carnea and spiders.